Nestling growth and body condition of critically endangered Orange-bellied Parrots Neophema chrysogaster. (2nd April 2020) - Stojanovic, Dejan; Alves, Fernanda; Webb, Matthew H.; Troy, Shannon; Young, Catherine M.; Rayner, Laura; Crates, Ross; Cook, Henry; Heinsohn, Rob
ABSTRACT: Intervening when bird nestlings are performing poorly relative to the population mean may be a management priority if individuals are of high-conservation value. Assessing body condition may enable identification of potential problems before they cause mortality. We aimed to provide a tool for conservation managers to identify underperforming nestlings in a severely threatened bird population. We develop models of nestling growth and empirically quantify nestling body condition of critically endangered Orange-bellied Parrots Neophema chrysogaster, which have declined to only a single population in southwestern Tasmania, Australia. Using census data on growth of nestlings born over four years into the contemporary wild population, we test whether a body condition index is influenced by sex, hatch order, year of birth, brood size, whether one or both parents were captive bred, and fledging date. The best model describing body condition in Orange-bellied Parrot nestlings included additive effects of year of birth and hatch order. Nestling body condition was lowest in 2013, where first hatched nestlings were 2.5 g lighter than those born in 2016, and > 4.2 g lighter than in 2017/18. Nestlings that hatched either first or in the middle of the brood were respectively 4.8 g and 3.8 g heavier than last-hatched birds. Our body condition index provides a repeatable, rapid and cheap way to assess body condition of wild Orange-bellied Parrot nestlings. This represents a step towards accurate evaluation of management actions aimed at improving reproductive outcomes for this species, and provides a framework for developing hypotheses to test using an empirical and measurable index of individual quality.